EFEKTIVITAS KEBIJAKAN ALOKASI DANA DESA BAGI PEMBANGUNAN EKONOMI PERDESAAN - Rita Kusmunawati; S Syafruddin (Pusat Riset dan Publikasi, 2023)
This study aims to determine the effect of village fund allocation policies on rural economic development in Luk Village, Rhee Sub-District, Sumbawa District. This type of research is associative research which aims to determine the relationship or influence between two or more variables. The type of data used is quantitative data obtained from the results of scoring on respondents' answers related to research problems. Data obtained directly from respondents through a questionnaire. This research is a sample research, in which researchers took a sample of 95 people as representatives of a total population of 1,940 people. The data that has been collected is processed using the SPSS program for further analysis and interpretation using simple linear regression analysis techniques, partial parameter hypothesis testing (t test), and determination coefficient test (R2). The results showed that the village fund allocation policy had a positive and significant effect on rural economic development in Luk Village, Rhee Sub-District, Sumbawa District. That is, the greater the allocation of village funds in development, the rural economic growth in Luk Village, Rhee Sub-District, Sumbawa District will also increase, and vice versa. The ability of village fund allocation policy variables to explain variations in changes in rural economic development variables in Luk Village, Rhee Sub-District, Sumbawa District is 35.6%, while the remaining 64.4% is influenced by other variables outside this research model.